2012
DOI: 10.5944/rppc.vol.17.num.3.2012.11845
|View full text |Cite
|
Sign up to set email alerts
|

Propuestas para un enfoque transdiagnóstico de los trastornos mentales y del comportamiento: Evidencia, utilidad y limitaciones = Proposals for a transdiagnostic perspective of mental and behavioural disorders: Evidence, usefulness, and limitations

Abstract: Resumen: Las elevadas tasas de comorbilidad y covariación entre los diversos trastornos mentales constituyen una de las limitaciones más importantes de los actuales sistemas de diagnóstico psiquiátrico, que además están basados en categorías definidas por sus características clínicas y no en supuestos etiológicos. Estas limitaciones se ponen especialmente de manifiesto en el caso de los trastornos de ansiedad y depresivos, y se producen también en los trastornos alimentarios. La acumulación de evidencias sobre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 38 publications
2
2
0
11
Order By: Relevance
“…The findings showed that more than half of the non-clinical community participants had experienced illness-ITs in the past three months, although their frequency was generally low ('occasionally'). Nonetheless, it was noteworthy that the reported frequency was identical to what was observed for intrusive thoughts with obsessional contents in community samples (Belloch, Roncero, & Perpiñ a, 2016), which supports the notion that intrusive thoughts can be viewed as transdiagnostic variables and might be considered vulnerability factors in different disorders (Belloch, 2012;Pascual-Vera & Belloch, 2018a;Pascual-Vera, Roncero, & Belloch, 2017;Romero-Sanchiz et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…The findings showed that more than half of the non-clinical community participants had experienced illness-ITs in the past three months, although their frequency was generally low ('occasionally'). Nonetheless, it was noteworthy that the reported frequency was identical to what was observed for intrusive thoughts with obsessional contents in community samples (Belloch, Roncero, & Perpiñ a, 2016), which supports the notion that intrusive thoughts can be viewed as transdiagnostic variables and might be considered vulnerability factors in different disorders (Belloch, 2012;Pascual-Vera & Belloch, 2018a;Pascual-Vera, Roncero, & Belloch, 2017;Romero-Sanchiz et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…Se pretende con ello solventar algunas de las limitaciones derivadas de los sistemas categoriales, tales como la dificultad para establecer diagnósticos precisos, las altas tasas de comorbilidad (tanto intra-como entre-categorías), la «mutación» de un trastorno en otro, las dificultades para establecer etiopatogenias específicas y diferenciadas, y como consecuencia de todo ello, los problemas para establecer el curso de los distintos trastornos y las pautas más eficaces para su tratamiento. El cumplimiento de estos objetivos deberá por tanto optimizar los recursos y procesos de evaluación, diagnóstico y tratamiento (Aldao y Nolen-Hoeksema, 2010;Barlow et al, 2011;Belloch, 2012;Fairburn, Cooper, y Shafran, 2003;Nolen-Hoeksema y Watkins, 2011).…”
Section: Introductionunclassified
“…17, nº 3). Las intrusiones mentales desagradables y no deseadas (en adelante, IM) se encuentran entre las posibles variables transdiagnósticas de la psicopatología que nuestro grupo viene proponiendo (p.ej., Belloch, 2012). Si bien se ha constatado la relevancia de las IM como análogos y/o pre-síntomas clínicos en el trastorno obsesivo-compulsivo, también se ha mencionado que su aparición y relevancia van más allá de este trastorno.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…One of the main problems of the categorical approach to psychopathology is the high comorbidity among the different mental disorders (Sandín et al, 2012). In last years, a new approach has emerged for the treatment of mental disorders that aims to develop interventions that can be used to treat the common symptoms of various psychological disorders (Belloch, 2012). This approach, known as transdiagnostic, considers that mental disorders share numerous cognitive and behavioral processes that contribute to the development and maintenance of symptoms (Harvey et al, 2004).…”
Section: Introductionmentioning
confidence: 99%